Patronage and Use of Library Resources among Gen Z Undergraduates in Nigerian Universities - Okwu, Emmanuel; Oyighan, Diseiye; Oladokun, Bolaji (MO.RI Publishing, 2025)
This paper investigates the patronage and use of library resources among Generation Z undergraduates in Nigerian universities. With the increasing influence of digital technologies, academic libraries face challenges in maintaining relevance for Gen Z students, who exhibit a strong preference for digital platforms and self-directed learning. The study aimed to determine the extent of library patronage, identify frequently used library resources, analyze factors influencing library use, explore the role of digital alternatives, and suggest strategies to enhance library engagement. A cross-sectional descriptive survey was employed, targeting undergraduates from five Nigerian universities. Data were collected using a structured questionnaire based on a four-point Likert scale, and responses from 219 students were analyzed using descriptive statistics. Findings revealed low levels of library patronage, with students favoring digital resources, social media, and e-learning platforms over traditional library services. No single library resource was frequently utilized, with institutional repositories and thesis collections being the most accessed. Key factors influencing non-use included limited accessibility, inadequate ICT infrastructure, and inconvenient library hours. Students strongly advocated for digital transformation, recommending social media integration, AI-driven assistance, and mobile-friendly library services. The study concludes that academic libraries must modernize their services to align with Gen Z’s digital preferences. Recommendations include expanding digital resources, improving ICT infrastructure, integrating social media, and personalizing library services to enhance user engagement and relevance.